2006
DOI: 10.1086/506973
|View full text |Cite
|
Sign up to set email alerts
|

A Phylogenetic Analysis of Sleep Architecture in Mammals: The Integration of Anatomy, Physiology, and Ecology

Abstract: Among mammalian species, the time spent in the two main "architectural" states of sleep--slow-wave sleep (SWS) and rapid-eye-movement (REM) sleep--varies greatly. Previous comparative studies of sleep architecture found that larger mammals, those with bigger brains, and those with higher absolute basal metabolic rates (BMR) tended to engage in less SWS and REM sleep. Species experiencing a greater risk of predation also exhibited less SWS and REM sleep. In all cases, however, these studies lacked a formal phyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
191
7
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(204 citation statements)
references
References 120 publications
(136 reference statements)
3
191
7
3
Order By: Relevance
“…Based on these considerations, the use of sleep quotas has long been a standard measure used in comparative tests, (Elgar AB 1988) [11] (Elgar AB 1990) [12] (Lesku AN 2006) [13] (Zepelin ES 1989) [14] and is the basis for construction of our database on sleep quotas.…”
Section: Validity Of Sleep Quotas In Comparative Analysesmentioning
confidence: 99%
“…Based on these considerations, the use of sleep quotas has long been a standard measure used in comparative tests, (Elgar AB 1988) [11] (Elgar AB 1990) [12] (Lesku AN 2006) [13] (Zepelin ES 1989) [14] and is the basis for construction of our database on sleep quotas.…”
Section: Validity Of Sleep Quotas In Comparative Analysesmentioning
confidence: 99%
“…For example, Capellini et al (2008a) found that sleep durations are shortened when animals have high metabolic rates for their body size, consistent with foraging constraints that limit the time available for sleep. Capellini et al (2008a) also found that when animals are more exposed to predation at sleep sites, their sleep durations decline (see also 3 Allison & Cicchetti 1976;Lesku et al 2006). In another study, these authors used phylogenetic methods to investigate the factors that influence the phasing of sleep (Capellini et al 2008b; see also Tobler 1989;Ball 1992).…”
mentioning
confidence: 99%
“…One recent comparative study, for example, found that the number of white blood cells covaries positively with sleep durations across species ), while other studies found that sleep characteristics covary with aspects of brain size (Lesku et al 2006;Capellini et al 2009). Many recent phylogenetic comparative studies have focused on sleep duration, including the duration of rapid eye movement (REM) and non-rapid eye movement (NREM) sleep (e.g., Lesku et al 2006;Capellini et al 2008a). Other fundamental questions concern the phasing of sleep throughout the 24-hour cycle (Tobler 1989;Ball 1992).…”
mentioning
confidence: 99%
See 2 more Smart Citations